Evidence map of pancreatic surgery: protocol for a living systematic review and meta-analysis - Probst, Pascal (BMJ Open, 2019)
INTRODUCTION: Pancreatic surgery is a large and complex field of research. Several evidence gaps exist for specific diseases or surgical procedures. An overview on existing knowledge is needed to plan and prioritise future research. The aim of this project is to create a systematic and living evidence map of pancreatic surgery. METHODS AND ANALYSIS: A systematic literature search in MEDLINE (via PubMed), Web of Science and Cochrane Central Register of Controlled Trials will be performed searching for all randomised controlled trials (RCT) and systematic reviews (SR) on pancreatic surgery. RCT and SR will be grouped in research topics. Baseline and outcome data from RCT will be extracted, presented and effect sizes meta-analysed. Data from SR will be used to identify evidence gaps. A freely accessible web-based evidence map in the format of a mind map will be created. The evidence map and meta-analyses will be updated periodically. DISSEMINATION: After completion of the project, a permanently updated evidence map of pancreatic surgery will be available to patients, physicians, researchers and funding bodies via www.evidencemap.surgery. Its use will allow clinical decision-making based on primary data and prioritisation of future research endeavours. PROSPERO REGISTRATION NUMBER: CRD42019133444.